Migração do ensino presencial para plataformas mediadas por tecnologias digitais: a visão dos alunos e professores - Mello, Julia Brum de (2022)
Introduction: The end of 2019 was marked by the emergence of a new disease, the COVID-19, which quickly spread throughout the world, determining an unusual pandemic situation due to its speed of transmission and potential severity. The contagion mechanism implied the need for social isolation. Thus, the exceptionality in health care and the closure of community activities was established. This situation implied a sudden change in teaching-learning strategies in all levels of education at the beginning of 2020. What was expected to be a short and transitory period turned out to be a prolonged situation, the teaching of health professions was especially harmed, as the very health care system was compromised. Higher Education Institutions had to adapt to remote teaching. The Pontifical Catholic University of São Paulo (PUC-SP), specifically in its medicine and nursing courses, sought to adjust quickly to remotely guarantee the continuity of teaching and the fulfillment of pedagogical projects, seeking to minimize losses for students and to the University. Objectives: Thus, this study aimed to evaluate the consequences to the teachinglearning process in the undergraduate medical course at FCMS at PUC-SP imposed by the change from face-to-face teaching to communication platforms in synchronous digital environments, after the closing of the campus and the other teaching scenarios of FCMS at PUC-SP. Subjects and methods: We investigated how the students of the first, second and third years of the medical course evaluated the different aspects of teaching and learning after switching activities to synchronous digital platforms, as well as the summative assessment at the end of the first module that was performed remotely. In addition, we investigated how the professors who worked from the first to the third year of the medical course evaluated the different aspects of teaching and learning after the change of activities to synchronous digital platforms and the process of summative evaluation of the first module carried out on synchronous digital platforms. This was an exploratory, cross-sectional study, but with a recent retrospective reference, of a qualitative and quantitative nature, which used the questionnaire developed on the Google Forms® platform and open questions as an instrument. The descriptive analysis of the data obtained through the Likert scale questionnaires were considered as non-parametric and submitted to the analysis by the Chi-square test (we considered significant the results obtained with p≤0.05). The 8 answers to the open questions were analyzed and categorized according to Bardin. The questionnaire was answered by 85 students in the first year (85%) and 110 students (58.5%) in the second and third years. The teachers only answered the questions regarding the activities in which they worked. They were: 18 tutors (75% of the total number of tutors), 16 skills teachers (61%), 11 PAS teachers (68%), 18 mentors (62%). Results: The reports about the beginning of remote emergency teaching allow us to observe that academic activity was a reason for anguish due to uncertainties; the idea of institutional helplessness is also felt in this group of students. The educational institution, which should be a catalyst for critical discussions about reality, also seems to go through a process of adaptive difficulty. The study points out that the lack of adequate electronics and teachers who are not proficient in specific knowledge and techniques impact student engagement. Class duration also requires adaptation to the remote teaching model, shorter classes keep the student attentive, in addition to the use of methodologies that are not exclusively expository. These more specific trainings did not take place in college and were reflected both in the teachers' comments regarding the insecurity of the method, as well as in the students' regarding the unprofitable long classes, lack of teacher preparation, lack of available feedback. Like all research work, our study has strengths and limitations. We understand that one of the strengths of this work is to share the results of a formal survey, at a time when most publications correspond to the authors' experience reports, opinions and comments. Another positive point is being able to make this data available to the academic community in time to be seen and analyzed in order to contribute to the academic planning of the year 2022, a complete unknown from an educational point of view